Calibration of partial factors for actions in the Eurocodes accounting for biases in climatic load maps - Formichi, Paolo; Croce, Pietro; ICASP14; Landi, Filippo (My University, 2023)
In view of the development of the 2nd generation of structural Eurocodes, a discussion on standard optimization by means of the calibration of partial factors for actions is currently ongoing. In the paper, the calibration of partial factors for permanent and variable loads is discussed, with a specific focus on the role of hidden safeties, which are generally introduced in the design according to the National Annexes to the Eurocodes when dealing with climatic actions. A procedure to account for a safe-sided bias in snow and wind maps, which is found relevant for several countries in Europe, is presented. The influence of the detected biases in the evaluation of reliability levels and the calibration of partial factors is thus investigated with reference to a portfolio of representative structures and limit states, including six different materials and mechanical properties governing the design resistance (structural steel yield strength, concrete compressive strength, re-bar yield strength, glulam timber bending strength, solid timber bending strength, and masonry compressive strength). The results confirm the importance to properly account for such safe-sided assumptions in the calibration process, following a consistent approach with the definition of climatic load maps at national level.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED